Quality of Life After Laser Vision Correction: A Systematic Review and Meta-Analysis - Alireza Peyman; Matin Irajpour; Maryam Yazdi; Farzaneh Dehghanian; Pegah Noorshargh; Yasaman Broumand; Farnaz Fatemi; Mohsen Pourazizi (Journal of Ophthalmology)
Conclusion: Patients undergoing LVC experience significant improvements in QOL, particularly in younger subjects, and achieve comparable QOL to individuals with emmetropia.